Picture Book of Surabaya Legend Supports EFL Vocabulary and Cultural Learning - Achmad Bachtiar Pribadi; Vidya Mandarani (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: In English as a Foreign Language (EFL) contexts, printed teaching materials that integrate textual and visual information are widely used to support comprehension, motivation, and cultural awareness. Specific Background: Picture books that combine narrative text with illustrations provide scaffolding for understanding story progression, vocabulary, and moral values, particularly when adapted from familiar local narratives. Knowledge Gap: Despite the recognized potential of visual narrative materials, locally grounded picture books designed specifically for EFL vocabulary learning and cultural connection remain underutilized. Aims: This study developed and implemented a simplified English picture book based on the Surabaya legend to support vocabulary acquisition and narrative comprehension. Results: The Picture Book – The History of Surabaya integrates sequential illustrations with short sentences, enabling classroom activities such as reading aloud, story sequencing, retelling, vocabulary identification, and group discussion. The combined use of words and images helps learners comprehend narrative structure, expand word meaning, practice narration, and engage with moral messages while connecting local heritage to language learning. Novelty: The material embeds local folklore into an English learning resource, linking linguistic development with intercultural awareness and identity formation. Implications: The findings suggest that culturally based picture books can serve as practical supplementary materials for EFL classrooms, supporting reading comprehension, vocabulary development, narrative skills, and cultural understanding in an engaging and meaningful way.Highlights: Sequential illustrations facilitate comprehension of story structure and word meaning. Classroom practices include oral reading, panel ordering, discussion, and dramatized retelling. Local folklore integration connects language study with heritage awareness and moral learning. Keywords: Picture Book; EFL Vocabulary Learning; Narrative Text; Cultural Literacy; Visual Learning Media